'Listening' to the Neanderthals in William Golding's The Inheritors: A sociopragmatic approach to fictional dialogue. (June 2018) - Mandala, Susan
Highlights: A sociopragmatic analysis of the Neanderthal dialogue in The Inheritors . The analysis shows that the Neanderthal characters make complex inferences. The analysis shows the Neanderthal characters have theory of mind. The analysis shows the Neanderthal characters show higher orders of intentionality. Abstract: In their work on William Golding's fiction, Kinkead-Weekes and Gregor (1967) claim that The Inheritors, more concerned with matters of mythic significance, forfeited "most of the possibilities of the dialogue" (71). While in-depth treatments of language in Golding's The Inheritors have since been offered (Halliday, 1971; Hoover, 1999; Clark, 2009), the "possibilities of the dialogue, " in particular the conversational register of the Neanderthal characters, remain largely neglected. In this sociopragmatic re-reading of The Inheritors, I employ theory of mind and intentionality (as outlined in Dunbar (2004) as analytical tools in order to 'listen' more closely to the Neanderthals in Golding's text. Paying particular attention to these characters as they express their religious beliefs, engage in storytelling, and work through interpersonal conflicts, I argue that readers are invited to infer that the Neanderthal characters are themselves inferring beings, and further demonstrate that this interpretation has implications not only for how individuals approach the novel, but for the way The Inheritors as a cultural text can be understood to participate in discursively mediating our relationship with the figure of the Neanderthal.